EXPERTISE, WISDOM AND MORAL PHILOSOPHERS: A RESPONSE TO GESANG - Cowley, Christopher (Bioethics, 2012)
In a recent issue of Bioethics, Bernard Gesang asks whether a moral philosopher possesses greater moral expertise than a non-philosopher, and his answer is a qualified yes, based not so much on his infallible access to the truth, but on the quality of his theoretically-informed moral justifications. I reject Gesang's claim that there is such a thing as moral expertise, although the moral philosopher may well make a valid contribution to the ethics committee as a concerned and educated citizen. I suggest that wisdom is a lot more interesting to examine than moral expertise. Again, however, moral philosophers have no monopoly on wisdom, and the study of philosophy may even impede its cultivation.